The andes of bladder stones: Gigantic bladder calculi in a patient with bladder outlet obstruction and hyperparathyroidism - Halimat A. Olaoluwa; Hari Polenakovik; Jonathan Hakim (Urology Case Reports, 2023)
60-year-old man with known chronic urinary retention (CUR) managed with clean intermittent catheterization (CIC); He presented with difficulty with CIC. A KUB revealed 13 cm in conglomeration bladder stones. Routine preoperative bloodwork revealed calcium >12 and a subsequent PTH was also elevated. Osteoporosis was confirmed on DEXA. Sestamibi parathyroid scan had increased uptake within one parathyroid gland. The patient underwent open suprapubic 92 gm prostatectomy with evacuation of 254 gm calcium phosphate bladder stones; this was followed by removal of the offending parathyroid gland. On follow up, the patient was voiding well with normalization of other symptoms related to hyperparathyroidism.